Crossing actors' boundaries towards circular ecosystems in the organic food sector: Facing the challenges in an emerging economy context. (25th June 2023) - Ferrari, Aline Gabriela; Jugend, Daniel; Armellini, Fabiano; Barbalho, Sanderson César Macedo; Carvalho, Marly Monteiro de
Abstract: The demand for organic food is increasing worldwide. Studies have shown that the circular economy can bring environmental and operational improvements to the food sector. However, little is known about how the circular economy can contribute to organic food. From the perspective of circular ecosystems, this exploratory study aims to contribute to the emerging debate by identifying and analyzing the relationships between different actors in an ecosystem of organic food producers. Addressing this objective, a case study was carried out involving seven actors from an organic food ecosystem in Brazil. The main results revealed: (i) that the production of organic food is aligned with the principles of the circular economy; (ii) that the common goal of using and disseminating organic agriculture facilitates alignment between the actors in an ecosystem; (iii) the important role of the orchestrator, mainly to coordinate the different actors and technically support small producers/farmers; and (iv) that collaboration in an ecosystem favors the reuse of "waste" between farmers. In addition, our results identified that ecosystems face bureaucratic barriers to obtaining resources, and there is little collaboration between the actors and universities. Highlights: The circular ecosystem concept is investigated in the organic food sector. The orchestrator plays an important role in the governance of the ecosystem investigated. The common objective of using and disseminating organic agriculture facilitates alignment between the actors. The integration between the actors has facilitated the adoption of practices related to the circular economy.